The high prevalence and impact of rheumatic heart disease in pregnancy in First Nations populations in a high‐income setting: a prospective cohort study - Sullivan, EA; Vaughan, G; Li, Z; Peek, MJ; Carapetis, JR; Walsh, W; Frawley, J; Rémond, MGW; Remenyi, B; Jackson Pulver, L; Kruske, S; Belton, S; et al. (BJOG : an international journal of obstetrics and gynaecology, 2020)
Objective To describe the epidemiology of rheumatic heart disease (RHD) in pregnancy in Australia and New Zealand (A&NZ). Design Prospective population‐based study. Setting Hospital‐based maternity units throughout A&NZ. Population Pregnant women with RHD with a birth outcome of ≥20 weeks of gestation between January 2013 and December 2014. Methods We identified eligible women using the Australasian Maternity Outcomes Surveillance System (AMOSS). De‐identified antenatal, perinatal and postnatal data were collected and analysed. Main outcome measures Prevalence of RHD in pregnancy. Perinatal morbidity and mortality. Results There were 311 pregnancies associated with women with RHD (4.3/10 000 women giving birth, 95% CI 3.9–4.8). In Australia, 78% were Aboriginal or Torres Strait Islander (60.4/10 000, 95% CI 50.7–70.0), while in New Zealand 90% were Māori or Pasifika (27.2/10 000, 95% CI 22.0–32.3). One woman (0.3%) died and one in ten was admitted to coronary or intensive care units postpartum. There were 314 births with seven stillbirths (22.3/1000 births) and two neonatal deaths (6.5/1000 births). Sixty‐six (21%) live‐born babies were preterm and one in three was admitted to neonatal intensive care or special care units. Conclusion Rheumatic heart disease in pregnancy persists in disadvantaged First Nations populations in A&NZ. It is associated with significant cardiac and perinatal morbidity. Preconception planning and counselling and RHD screening in at‐risk pregnant women are essential for good maternal and baby outcomes. Tweetable Rheumatic heart disease in pregnancy persists in First Nations people in Australia and New Zealand and is associated with major cardiac and perinatal morbidity. Tweetable Rheumatic heart disease in pregnancy persists in First Nations people in Australia and New Zealand and is associated with major cardiac and perinatal morbidity.